Implementing the Missouri Mathematics Project Learning Model to Enhance Students’ Physics Problem-Solving Skills - Desy Shafira Siahaan; Muhammad Syukri; Evendi Evendi; Susilawati Susilawati; Erni Maidiyah; Fitria Herliana (AL-ISHLAH: Jurnal Pendidikan, 2025)
Problem-solving is a critical competency for students, particularly in physics education. However, observations and literature reviews indicate that students' physics problem-solving abilities remain low. This deficiency is often linked to underdeveloped mathematical skills, which are essential for understanding and applying physics concepts. This study aims to analyze the significant differences in students' physics problem-solving abilities between those taught using the Missouri Mathematics Project (MMP) model and those taught using conventional instructional methods. This quasi-experimental research employed a nonequivalent control group design. The study was conducted at Madrasah Aliyah Negeri (MAN) Tanjungbalai with a population of 95 students. A purposive sampling technique was used to select 47 students, divided into experimental and control groups. The instruments used were a physics problem-solving test consisting of five essay questions and a student response questionnaire. Data were analyzed using the independent t-test.Findings reveal that students in the experimental group, taught using the MMP model, demonstrated significantly higher problem-solving ability than those in the control group. This is evidenced by the N-Gain scores: the experimental class achieved an average N-Gain of 0.74, compared to 0.51 in the control class.The results indicate that the MMP model positively influences students' physics problem-solving skills. The structured and collaborative nature of MMP may enhance conceptual understanding and application, suggesting its potential as an effective teaching strategy in physics education.